Designed activities on developing mental strategies using alms value-based learning trajectory in elementary school - Mariana, Neni; Sasmita, Febriarsita Eka (Journal on Mathematics Education, 2024)
Mental strategies are recognized as an effective approach for solving arithmetic operations such as addition and subtraction. This study focuses on developing and implementing instructional activities aimed at enhancing students' mental strategy skills through the Indonesian Realistic Mathematics Education (IRME) approach. The research employed a design-based methodology involving 2nd-grade students from an Islamic-integrated school in Surabaya. The study followed a research design that emphasizes the development of local instructional theory, encompassing three key phases: the preparatory phase (initial design development), the experimental phase (classroom teaching experiments), and the retrospective analysis phase. Data collection methods included documentation, field notes, and interviews. In the first trial, three instructional activities were conducted. Based on the analysis of the first trial, the number of activities in the second trial was increased to four: "Let's Get Used to Alms Every Day," "Don't Forget Routine Alms This Week," "Set Your Own Pocket Money," and "Let's Give Away Your Alms to Break Mr. Samad’s Fast." These activities were designed to achieve specific mathematical objectives, enabling students to understand and solve addition and subtraction problems using strategies such as skip counting, borrowing, and saving. The retrospective analysis concluded that students successfully learned to perform addition and subtraction operations on both monetary values and ordinary numbers within the designed learning trajectory.